Factors related to sensory properties and consumer acceptance of vegetables. Issue 10 (31st May 2021) - Hoppu, Ulla; Puputti, Sari; Sandell, Mari
Abstract: Many consumers perceive the bitter taste or other sensory characteristic of vegetables as unpleasant, posing a challenge to dietary recommendations aiming to increase vegetable consumption. Food experience is multisensory, with complex interactions between the senses and individual differences in sensory perception. This review focuses on the factors affecting sensory properties of vegetables and sensory perception of vegetables among adults. Topical examples of sensory quality and evaluation of vegetable samples are presented. Cultivar and growing conditions are related to the internal sensory quality of vegetables. The effects of different processing methods, such as freezing and cooking, on the sensory properties of vegetables are also reviewed. Flavor modification of vegetables with seasonings may be used to improve palatability and incorporating vegetables to meals may increase the intake of vegetables. Recently, external factors (e.g. visual and odor stimuli) have been tested in multisensory research in the context of vegetable perception and choice. These options to achieve better sensory quality, more palatable meals and pleasant eating context may be used to promote vegetable intake among adults.